The Many roles of PGC-1α in Muscle – Recent Developments - Chan, Mun Chun (2014)
Skeletal muscle is the largest organ in the body and contributes to innumerable aspects of organismal biology. Muscle dysfunction engenders numerous diseases, including diabetes, cachexia, and sarcopenia. At the same time, skeletal muscle is also the main engine of exercise, one of the most efficacious interventions for prevention and treatment of a wide variety of diseases. The transcriptional coactivator PGC-1α has emerged as a key driver of metabolic programming in skeletal muscle, both in health and disease. We review here the many aspects of PGC-1α function in skeletal muscle, with a focus on recent developments.